MARITAL QUALITY AND THE RELATIONSHIP BETWEEN CLOSENESS OF MARRIAGE PARTNERS AND CONFLICT RESOLUTION - Maria, Ryś (Studia Psychologica: Theoria et praxis, 2004)
The conducted research concerned the relationship between the level of closeness and methods of conflict resolution in marriages, which have succeeded or failed. 60 married couples (two groups) were chosen out of 500 studied persons, not exceeding age 50. In these two groups, research was conducted in order to determine the closeness of the marriage in the area of intellect, emotions and activity. Among the group of successful marriages, the level of closeness was high and conflicts were resolved in an integrating manner, which strengthens the couple's unity. The effects were opposite among the failed marriages, with conflict resolution leaving behind a sense of loneliness, misunderstanding and grief.